2005
DOI: 10.1128/mcb.25.13.5317-5328.2005
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-Mediated Transcription: Ligand-Dependent Recruitment of Estrogen Receptor α to 2,3,7,8-Tetrachlorodibenzo- p-Dioxin-Responsive Promoters

Abstract: Using chromatin immunoprecipitation assays, we studied the 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-mediated recruitment of the aryl hydrocarbon receptor (AhR) and several coregulators to the CYP1A1 promoter. AhR displayed a time-dependent recruitment, reaching a peak at 75 min and maintaining promoter occupancy for the remainder of the time course. Recruitment of AhR was followed by TIF2/SRC2, which preceded CBP, histone H3 acetylation, and RNA polymerase II (RNAPII). Simultaneous recruitment to the enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
161
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 60 publications
20
161
1
Order By: Relevance
“…AhR-mediated gene transcription is modulated via direct recruitment of estrogen receptor-a, which links estradiol activity to AhRdioxin-mediated signaling (30,31). This and other associated pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…AhR-mediated gene transcription is modulated via direct recruitment of estrogen receptor-a, which links estradiol activity to AhRdioxin-mediated signaling (30,31). This and other associated pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assays were performed according to Matthews et al (2005) except that 100 to 120 mg of snap-frozen liver was homogenized and cross-linked in 1% formaldehyde, and the DNA was isolated using a PCR purification kit (BioBasic, Inc., East Markham, ON, Canada) and eluted in 50 l. ChIP DNA (1 l) was amplified by PCR with primers 5ЈAAGCCAAGC-CAGAAAATCAA3Ј and 5ЈTCGAGGAACAGAGTGCAATG3Ј for the mouse Fmo3 AHRE (Ϫ3183 to Ϫ3260 relative to the transcriptional start site). For real-time PCR, Power SYBR Green PCR Master Mix was used to amplify the DNA fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TCDD increases the DNA-binding activity of the ER independent of estrogen in the rat uterus (Chaffin et al, 1996), and treatment of MCF-7 cells with TCDD results in G 0 /G 1 to S-phase transition and estrogen like mitogenic effects (Abdelrahim et al, 2003). Studies have also shown that ER and AhR interact (Brunnberg et al, 2003;Beischlag and Perdew, 2005), and there is a discrepancy as to the coactivator or corepressor function of ER on AhR/ARNTmediated induction of Cyp1a1 (Beischlag and Perdew, 2005;Matthews et al, 2005). Reports also indicate that the ligandactivated AhR/ARNT associates with the unliganded ER to form a functional complex that binds EREs (Ohtake et al, 2003).…”
Section: Dioxin Induces An Estrogen-like Gene Expression Response 1603mentioning
confidence: 99%